Effects of combined strength and aerobic training on middle and long-distance performance: A meta-analysis - Berryman, N.; Mujika, I.; Binet, C.; Roubeix, M.; Bosquet, L. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Combined strength and aerobic training is an appropriate strategy to decrease the energy cost of locomotion (ECL), improve aerobic endurance (AE) and may enhance performance in middle and long distance events (1, 2). The aim of this study was to assess the effects of strength training on middle and long-distance performance through a meta-analysis of the available literature. METHODS: Articles were included in this meta-analysis if they met these criteria: 1) combined strength and aerobic training; 2) performance outcomes (official or simulated competition, maximal oxygen uptake - VO2max, ECL or AE) related to middle and long-distance events in cross country skiing, running, triathlon, swimming, cycling, rowing and biathlon; 3) details about the training load; 4) sufficient information to calculate effect size. Thirty-seven articles were included. Statistical analyses were presented in detail in a previous article from members of our laboratory (3). RESULTS: Combined strength and aerobic training provides a moderate beneficial effect on middle and long-distance performance (SMD [95% CI] = 0.61 [0.43 to 0.79], P < 0.01). Combined training with a focus on maximal strength (0.26 [0.10 to 0.42], P < 0.01) or sub-maximal strength (0.57 [0.10 to 1.03], P < 0.01) had beneficial effects on VO2max. AE was also improved after implementation of sub-maximal strength training (2.8 [1.85 to 3.77], P < 0.01). Moreover, it was shown that ECL was significantly decreased (-0.75 [0.45 to 1.04], P < 0.01). A meta-regression analysis revealed that changes in middle and long-distance performance were associated with changes in VO2max (slope: 0.52, P < 0.05), AE (slope: 0.50, P < 0.01) and ECL (slope: = 0.58, P < 0.01). DISCUSSION: These results provide a framework that support the implementation of strength training in addition to normal aerobic training to improve middle and long-distance performance and associated aerobic characteristics.